Se Nanoparticles Induce Changes in the Growth, Antioxidant Responses, and Fruit Quality of Tomato Developed under NaCl Stress - Mónica Carolina Morales-Espinoza; Gregorio Cadenas-Pliego; Marissa Pérez-Alvarez; Alma Delia Hernández-Fuentes; Marcelino Cabrera de la Fuente; Adalberto Benavides-Mendoza; Jesús Valdés-Reyna; Antonio Juárez-Maldonado (Molecules, 2019)
Nanotechnology represents an opportunity to improve the use of elements in agriculture. Selenium is an element that is beneficial to plants and essential to the human diet. The size of nanoparticles gives them characteristics that can enhance the benefits that selenium provides to plants. The objective of the present study was to determine the effects of selenium nanoparticles on the growth, antioxidant responses, and fruit quality of tomato developed under NaCl stress. Four doses of selenium nanoparticles (1, 5, 10, and 20 mg L−1) under NaCl stress, only NaCl, and a control were evaluated. The results showed that the impact of salinity on the growth of the tomato crop can be reduced with the application of selenium nanoparticles. However, the amount of both enzymatic and non-enzymatic compounds significantly increased in the leaves and fruits of tomato. The results suggest that the application of selenium nanoparticles generated a positive effect against salinity in the tomato crop; moreover, it had a positive impact on the content of beneficial biocompounds for human health in tomato fruits.